2021
DOI: 10.3389/fvets.2021.696703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High-Grain Diet With a Buffering Agent on Milk Protein Synthesis in Lactating Goats

Abstract: Chinese dairy industries have developed rapidly, providing consumers with high-quality sources of nutrition. However, many problems have also appeared during the development process, especially the low quality of milk. To improve milk quality, a large amount of concentrated feed is usually added to the diet within a certain period of time, which increases the milk production to a certain extent. However, long-term feeding with high-concentration feed can lead to subacute rumen acidosis. Therefore, the present … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Despite the numerous analytical methods reported in the literature addressing the determination of both FFAs and protein-bound AAS, the chromatographic separation and determination of FAAs in complex matrices is still a challenge. In most of the recently published studies [30,38,[40][41][42][43][44] reported in Table S7 of the Supplementary Materials, importance has been given to the general impact of the AA content/profile on the physiopathological status of livestock animals, often in relation to nutritional intervention. However, in most of the cited papers, the analytical figures of merit of the applied methods are not considered/reported.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the numerous analytical methods reported in the literature addressing the determination of both FFAs and protein-bound AAS, the chromatographic separation and determination of FAAs in complex matrices is still a challenge. In most of the recently published studies [30,38,[40][41][42][43][44] reported in Table S7 of the Supplementary Materials, importance has been given to the general impact of the AA content/profile on the physiopathological status of livestock animals, often in relation to nutritional intervention. However, in most of the cited papers, the analytical figures of merit of the applied methods are not considered/reported.…”
Section: Discussionmentioning
confidence: 99%